O-046 Cerebral vasospasm following arteriovenous malformation rupture: a population-based cross sectional study. (23rd July 2022) - Dicpinigaitis, A; Feldstein, E; Shapiro, S; Kamal, H; Bauerschmidt, A; Rosenberg, J; Amuluru, K; Pisapia, J; Dangayach, N; Liang, J; Bowers, C; Mayer, S; et al.
Abstract : Introduction/Purpose: Limited evidence exists characterizing the incidence, risk factors, and clinical outcomes of arterial vasospasm secondary to cerebral arteriovenous malformation (cAVM) rupture. We utilize a population-based national registry to investigate this largely unexamined clinical entity. Materials and Methods: Weighted discharge data from the National Inpatient Sample during the period of 2015 to 2019 were queried to identify adult ruptured cAVM patients and subsequently those developing angiographically-confirmed vasospasm. Complex samples multivariable logistic regression and chi-square automatic interaction detection (CHAID) decision tree analyses were performed to identify significant associations between clinical covariates and the development of vasospasm, and a cAVM vasospasm predictive model (cAVM-VPM) was generated based on the effect sizes of these parameters. Results: Among 7, 215 cAVM patients identified, 935 developed vasospasm, corresponding to an incidence of 13.0%. 110 of these patients (11.8%) subsequently progressed to delayed cerebral ischemia (DCI). Multivariable adjusted modeling identified baseline clinical covariates [decreasing age (by decade) (aOR 0.87, 95% CI 0.83, 0.92; p < 0.001), female sex (aOR 1.68, 95% CI 1.45, 1.95; p < 0.001), admission Glasgow Coma Scale score < 9 (aOR 1.34, 95% CI 1.01, 1.79; p = 0.045), intraventricular hemorrhage (aOR 1.87, 95% CI 1.17, 2.98; p = 0.009), hypertension (aOR 1.77, 95% CI 1.50, 2.08; p < 0.001), obesity (aOR 0.68, 95% CI 0.55, 0.84; P < 0.001), congestive heart failure (aOR 1.34, 95% CI 1.01, 1.78; p = 0.043), tobacco smoking (aOR 1.48, 95% CI 1.23, 1.78; p < 0.019)] and hospitalization events [leukocytosis (aOR 1.64, 95% CI 1.32, 2.04; p < 0.001), hyponatremia (aOR 1.66, 95% CI 1.39, 1.98; p < 0.001), acute hypotension (aOR 1.67, 95% CI 1.31, 2.11; p < 0.001)] independently associated with the development of vasospasm. Intraparenchymal and subarachnoid hemorrhage were not associated with the development of vasospasm following multivariable adjustment. Among significant associations, a CHAID decision tree algorithm identified age 50–59 (parent node), hyponatremia, and leukocytosis as important determinants of vasospasm development. The cAVM-VPM achieved an area under the curve of 0.65 (sensitivity = 0.70, specificity = 0.53). Progression to DCI, but not vasospasm alone, was independently associated with in-hospital mortality (aOR 2.35, 95% CI 1.29, 4.31; p = 0.016) and lower likelihood of routine discharge (to home or to acute rehabilitation) (aOR 0.62, 95% CI 0.41, 0.96; p = 0.031) following adjustment for baseline covariates. Conclusion: This population-based analysis of vasospasm in cAVM identifies common clinical risk factors for its development and establishes progression to DCI as a predictor of poor neurological outcomes. Disclosures: A. Dicpinigaitis: None. E. Feldstein: None. S. Shapiro: None. H. Kamal: None. A. Bauerschmidt: None. J. Rosenberg: None. K. Amuluru: None. J. Pisapia: None. N. Dangayach: None. J. Liang: None. C. Bowers: None. S. Mayer: None. C. Gandhi: None. F. Al-Mufti: None.